THE INFLUENCE OF FLY ASH ON THE RELATIONSHIP BETWEEN AUTOGENOUS SHRINKAGE AND HYDRATION HEAT IN HIGH-PERFORMANCE CONCRETE (Jurnal Teknologi (Sciences & Engineering), 2024)
Autogenous shrinkage and heat of hydration are causes of premature cracking in HPC. Making high-performance concrete that has no cracks is a challenge. This research looks at the causes of these premature cracks and the impact of fly ash on these cracks. Observations were made on samples measuring 15 cm ´ 15 cm ´ 60 cm, 3 for HPC, and 3 for HPCfa with fc' 60 MPa. HPCfa is HPC where 10% of the binder is fly ash. One embedded strain gauge was installed on each sample at a distance of 5 cm from the sample. After the concrete was poured, the samples were covered with styrofoam for 24 hours and observations were made every 15 minutes. Data from 3 samples were processed using Dixon's criteria. The results showed that fly ash delays the peak heat of hydration by 4 hours, shortening the peak shrinkage duration to 30%, with a shrinkage value of 57% compared to HPC. Slowing down the occurrence of hydration peaks makes the concrete bond stronger so that it is more resistant to withstanding shrinkage peaks. The greatly reduced peak shrinkage duration means that the period of maximum suffering in young concrete is also shorter. The absence of fly ash means that the peak shrinkage does not immediately decrease because there is no osmotic pressure. Fly ash affects a hydration heat pattern similar to autogenous shrinkage (et). Both have a linear relationship Ht = 357216 et + C. The HPC similarity only reaches the peak of hydration.